The Impact of Productive Zakat on Improving the Welfare ofMustahik Micro EnterprisesAt the National ZakatAmil Agency (BAZNAS) Parepare City - Rachman, Mawaddah; Semaun, Syahriyah; Suarning, Suarning; Mahsyar, Mahsyar; Zubair, Muhammad Kamal (Universitas Muhammadiyah Makassar, 2024)
This researchaimsto analyze the methods and effect of effective zakat on improving the welfare of mustahik micro groupsat the Parepare metropolis country wide Zakat Amil organization. This studieschanged intoexecuted to BAZNAS leaders to find outproductive zakat tactics, even as to mustahik to find out the impact on improving the welfare of mustahik micro-firms. by way ofusing qualitative studiesmethods and subjectresearchtypes, as well asthe use of a case take a look atresearchtechnique. The statisticsobtainedmay be concluded that commercial enterprise capital from effective zakat given to mustahik can enhance the welfare of mustahik micro-businesses. the extent of mustahik welfare is seen from al-Ghazali's approach, particularly welfare primarily based on ad-Diin, an-Nafs, al-Aql, an-Nahl, and al-Mall.